Numerical Assessment of Gravity for Sloshing in Tank Using OpenFOAM (European Journal of Pure and Applied Mathematics, 2022)
We numerically study gravity’s effect on sloshing in a two-dimensional tank which is highly filled by water (95% water and 5% air). Both fluids are considered to be incompressible and inviscid. The surface tension and phase change are neglected. OpenFOAM software is used for the simulation. A standing wave of water impacting the lid of the tank at its center and a symmetric wetted region starts to advance along the lid. The simulation carried out (only on the right-half side of the tank due to symmetric geometry of the impact) with and without gravity to investigate the influence of gravity on this impact. The numerical results are validated by comparing to published data. The effect of gravity on the size of the wetted region, free-surface elevation and on the pressure distribution has been analyzed. It is shown that gravity is affecting the free-surface elevation and consequently the size of the wetted region. These effects growth as time goes. Pressure distribution along the wetted region of the lid is also influenced by gravity.
Keywords: Sloshing; Standing wave; Gravity; OpenFOAM